Controlled study of Escherichia coli diarrheal infections in Bangladeshi children. - Albert, M J (1995)
Diarrheal diseases are highly prevalent in Bangladesh. However, the relative contribution of diarrheagenic Escherichia coli organisms--those that are enterotoxigenic (ETEC), enteropathogenic (EPEC), enteroinvasive, enterohemorrhagic, enteroaggregative, and diffuse adherent--to diarrhea in Bangladeshi populations is not known. With DNA probes specific for these diarrheagenic E. coli strains, we analyzed fecal E. coli from 451 children up to 5 years of age with acute diarrhea seeking treatment at a Dhaka hospital and from 602 matched control children without diarrhea from July 1991 to May 1992. Enteroinvasive E. coli was not isolated from any children; enterohemorrhagic E. coli was not isolated from any diarrheal children but was isolated from five control children; enteroaggregative and diffuse adherent E. coli strains were isolated with similar frequencies from children with and without diarrhea, thereby showing no association with diarrhea; ETEC was significantly associated with diarrhea in the diarrheal children as a whole and especially in the age groups of 0 to 24 months and 37 to 48 months (further analysis suggests an association with diarrhea for the heat-stable toxin only and for both heat-labile- and heat-stable-toxin-producing ETEC only); and EPEC was significantly associated with diarrhea in the diarrhea group as a whole and particularly in infants up to 1 year of age. Further analysis suggested that EPEC strains of only the traditional serogroups were significantly associated with diarrhea. ETEC and EPEC infections peaked during warm months. Our data thus suggest that EPEC and ETEC are important causes of acute diarrhea in children in this setting.